DETECTION OF OXYTETRACYCLINE IN BROILER CHICKEN MEAT MARKETED IN SEVERAL CITIES IN JAVA ISLAND USING ENZYME-LINKED IMMUNOSORBENT ASSAY (ELISA) METHOD - Widiastuti, R.; Anastasia, Y. (Journal of the Indonesian Tropical Animal Agriculture, 2015)
Oxytetracycline (OTC) is one of the tetracycline (TCs) broad-spectrum antibiotics widely used inthe chicken industry. However, improper use of OTC with excessive doses potentially leads to residueformation in animal products that can be harmful to consumers in the form of allergic reaction orresistance. This study aimed to detect OTC residues in broiler chicken meat, marketed in traditionalmarkets and supermarkets in Depok, Bekasi, Bandung, Cilegon, Surakarta and Yogyakarta using indirectcompetitive enzyme-linked immunosorbent assay (icELISA) method. The analyses of 67 broiler meatsamples showed only 1 (1.5%) sample was positive for the OTC residue at 86.1 ng/g which meant belowthe maximum residue limits of permissible OTC (100 ng/g). Nevertheless, a stricter regulation for theuse of OTC in the poultry industry and the monitoring of its residue in chicken products prior tomarketing is still necessary to avoid the adverse effects of the residue present in animal products.